A MULTI-DIMENSIONAL ANALYSIS OF LOCAL PUBLIC SERVICE COSTS IN CENTRAL EUROPE - Polko, Adam; Baron, Marcin; Ochojski, Artur; Warzecha, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
A multi-dimensional approach to understanding spatial differences of public service costs in Central Europe is at the heart of the study. It has become especially challenging to identify the linkages to demographic, economic and other territorial aspects. The paper provides an implemented investigative model on service costs. It proves the success of overcoming local data technical and methodological bottlenecks; yet, unavailable across the European territory. The research is offered as a conceptual and empirical solution especially targeted at national and international statistical agencies supporting the policy-making processes.Business intelligence data has been obtained in pursuit of reliable estimations. Financial records of local service providers originating from private and public sectors across Central Europe have been analysed, allowing for the NUTS-3 aggregation of micro-data unavailable elsewhere. The analysis is based upon the calculation of proxy cost ratios (PCR) for social services and infrastructure (social care, health care and public housing) as well as network services and infrastructure (public transportation, roads, water and sewage). Consequently, the PCRs are tested against the correlation with demographic change, population density, GDP per capita and other socio-economic variables. Spearman's rank correlation coefficient has been used to test the dependence between variables. Compared to Pearson’s correlation coefficient, it allows better description of relationship between two variables in a situation when there are many anomalies (outlying observations). The final step allows identification of clusters of similar territories regarding tested variables. The taxonomy has been based upon Ward’s method and k-means algorithm. Further possibilities of interpretative spatial research have been offered.